Nutritional Sustainability Inside–Marketing Sustainability as an Inherent Ingredient - Bornkessel, Sabine; Smetana, Sergiy; Heinz, Volker (Frontiers in Nutrition, 2019)
Current discussions about the concept of nutritional sustainability show a high complexity of this topic leading to many different definitions. Regarding communication issues of nutritional sustainability between actors of food chains this complexity should be reduced. One opportunity to tackle these challenges of reducing complexity might be the concept of ingredient branding. Therefore, the aim of this mini-review is the identification of conditions for ingredient branding application as a communication strategy for nutritional sustainability which might overcome challenges in communicating the complexity between the different stakeholders of supply chains. In doing so, the specific case of agrifood chains is discussed based on the selected characteristics of globalization, increasing consumer demands, foods incorporating credence attributes and price. Along the agrifood chain, a sourcing strategy reflecting nutritional and sustainable aspects might lead to an ingredient branding strategy implying a brand policy for a special ingredient within the final product which is an important component but cannot be clearly recognized by the user. A “nutritional sustainability inside” strategy should reflect the multifaceted information along the agrifood chain and should be based on standardized criteria for nutritional sustainability.